Differential Models, Numerical Simulations and Applications - Bretti, Gabriella (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue includes 12 high-quality articles containing original research findings in the fields of differential and integro-differential models, numerical methods and efficient algorithms for parameter estimation in inverse problems, with applications to biology, biomedicine, land degradation, traffic flows problems, and manufacturing systems.